Is it the best for barista robots to serve like humans? A multidimensional anthropomorphism perspective - Kim, Taejin; Lee, One-Ki Daniel; Kang, Juyoung (International journal of hospitality management, 2023)
The COVID-19 pandemic has accelerated the use of contactless service robots in hospitality industries. However, the key drivers of consumer behaviors against service robots have been ill-understood. This study examines the interactive relationships between the physical (visual features) and psychological (service autonomy) dimensions of service-robot anthropomorphism and their impacts on consumer acceptance of service robots. Adopting an experimental vignette method (EVM) with 402 participants, the study reveals that the impacts of visual features on consumers’ intention are affected by the level of service robots’ autonomy; particularly, consumers showed the highest intention when the robots have medium visual features and high autonomy while their intention became lower for the same level of visual features with low autonomy. Interestingly, consumers showed the lowest intention with high level visual features, regardless of the levels of autonomy. Our results also show that human identity threats and consumer resistance play a significant counterproductive mechanism between service robot anthropomorphism and consumers’ intention. •A multidimensional perspective on the anthropomorphism of service robots.•Robot’s visual features as the physical dimension and autonomy as the psychological dimension.•Interactions effects between the visual features and autonomy on consumer’s intention to use.•Human identity threats and consumer resistance as another counterproductive social mechanism.•Use of an experimental vignette methodology to validate the theoretically proposed model.•A 3 × 2 between-subject experimental design (3 levels of visual features x 2 levels of autonomy).•Useful to the hospitality literature as more services become contactless using service robots.